Nutrient-supplemented propagation of Saccharomyces cerevisiae improves its lignocellulose fermentation ability - Marlous van Dijk; Friederike Mierke; Yvonne Nygård; Lisbeth Olsson (AMB Express, 2020)
Abstract Propagation conditions have been shown to be of considerable importance for the fermentation ability of Saccharomyces cerevisiae. The limited tolerance of yeast to inhibitors present in lignocellulosic hydrolysates is a major challenge in second-generation bioethanol production. We have investigated the hypothesis that the addition of nutrients during propagation leads to yeast cultures with improved ability to subsequently ferment lignocellulosic materials. This hypothesis was tested with and without short-term adaptation to wheat straw or corn stover hydrolysates during propagation of the yeast. The study was performed using the industrial xylose-fermenting S. cerevisiae strain CR01. Adding a mixture of pyridoxine, thiamine, and biotin to unadapted propagation cultures improved cell growth and ethanol yields during fermentation in wheat straw hydrolysate from 0.04 g g−1 to 0.19 g g−1 and in corn stover hydrolysate from 0.02 g g−1 to 0.08 g g−1. The combination of short–term adaptation and supplementation with the vitamin mixture during propagation led to ethanol yields of 0.43 g g−1 in wheat straw hydrolysate fermentation and 0.41 g g−1 in corn stover hydrolysate fermentation. These ethanol yields were improved compared to ethanol yields from cultures that were solely short-term adapted (0.37 and 0.33 g g−1). Supplementing the propagation medium with nutrients in combination with short-term adaptation was thus demonstrated to be a promising strategy to improve the efficiency of industrial lignocellulosic fermentation.